2011
DOI: 10.1007/s10295-011-0976-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of CbeI, a novel thermostable restriction enzyme from Caldicellulosiruptor bescii DSM 6725 and a member of a new subfamily of HaeIII-like enzymes

Abstract: Potent HaeIII-like DNA restriction activity was detected in cell-free extracts of Caldicellulosiruptor bescii DSM 6725 using plasmid DNA isolated from Escherichia coli as substrate. Incubation of the plasmid DNA in vitro with HaeIII methyltransferase protected it from cleavage by HaeIII nuclease as well as cell-free extracts of C. bescii. The gene encoding the putative restriction enzyme was cloned and expressed in E. coli with a His-tag at the C-terminus. The purified protein was 38 kDa as predicted by the 98… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 31 publications
3
56
0
Order By: Relevance
“…Cell-free extracts (CFE) were prepared from 1-liter cultures as described previously (7). Endonuclease assays were performed in 10-l reaction mixture volumes using 0.5 to 1 g of pJFW051 DNA.…”
Section: ϫ3mentioning
confidence: 99%
“…Cell-free extracts (CFE) were prepared from 1-liter cultures as described previously (7). Endonuclease assays were performed in 10-l reaction mixture volumes using 0.5 to 1 g of pJFW051 DNA.…”
Section: ϫ3mentioning
confidence: 99%
“…In developing methods for DNA transformation of C. bescii, we observed that restriction by a HaeIII isoschizomer, CbeI [21], was an absolute barrier to transformation of DNA from E. coli. We identified, cloned, expressed, and purified its cognate methyltransferase, M. CbeI, from C. bescii and showed that DNA methylated in vitro readily transformed C. bescii [17].…”
Section: Deletion Of the C Hydrothermalis Chyi Restriction Enzyme Rementioning
confidence: 99%
“…JWCH009 was grown to the late exponential phase (OD 680 approximately 0.15) in 50 mL LOD. Direct extraction of plasmid DNA from JWCH009 was performed as previously described [21,25]. The plasmid DNA was digested with enzymes HaeIII, EcoRI, HhaI, and MboI (NEB).…”
Section: Transformation Of C Hydrothermalis Jwch006mentioning
confidence: 99%
See 1 more Smart Citation
“…Such organisms require a tractable genetic system for metabolic engineering applications, and such a system has been established for C. bescii in recent years (5,6). A major step in developing a genetic system for C. bescii was the discovery that it has a restriction-modification system that severely limits its transformability (7). This barrier to transformation was overcome through the use of a methylated donor plasmid with a methylation pattern that protected the transformed DNA from restriction digestion (5).…”
mentioning
confidence: 99%